Medication-Related Osteonecrosis of the Jaws Bisphosphonates, Denosumab, and New Agents - Otto, Sven (Springer Berlin Heidelberg : Imprint: Springer, 2015)
Osteonecrosis of the jaws is a well-known side-effect of antiresorptive therapy that predominantly occurs in patients suffering from malignant diseases and receiving intravenous administrations of nitrogen-containing bisphosphonates or subcutaneous administrations of denosumab, a monoclonal antibody. Less frequently it may also be observed in patients with osteoporosis who are being treated with these antiresorptive drugs.  This textbook provides detailed, up-to-date information on all aspects of medication-related osteonecrosis of the jaws, including clinical features, pathogenesis, treatment options, and preventive measures. It also explains safe prevention and treatment strategies for patients receiving antiresorptive drugs who require extractions, implant insertions, and other dento-alveolar surgeries. This book will be of major interest for medical and dental students, dentists, and oral and maxillofacial surgeons as well as osteologists and oncologists.